1991
DOI: 10.1002/jsfa.2740550109
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of synthetic and potential natural antioxidants in improving the stability of sheep's anhydrous butter fat during long‐term storage

Abstract: A B S T R A C T Sheep's anhydrous butter fat was prepared by including separately wheat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Generally, 0.05% extracts were more effective than 0.02%. Several research groups have determined antioxidant and protective effects of sage and oregano and their extracts on fats and oils (Nakatani and Inatani 1984;Barbut et al 1985;Farag et al 1989;Amr 1991;Economou et al 1991;Banlas et al 1992;Boyd et al 1993;t)zcan and Akgul 1995). The PV at 0.02% oregano, 0.02% sage and 0.05% rosemary-sage added butter samples were similar to that of 0.02% BHA added samples at both 2% and 5c.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, 0.05% extracts were more effective than 0.02%. Several research groups have determined antioxidant and protective effects of sage and oregano and their extracts on fats and oils (Nakatani and Inatani 1984;Barbut et al 1985;Farag et al 1989;Amr 1991;Economou et al 1991;Banlas et al 1992;Boyd et al 1993;t)zcan and Akgul 1995). The PV at 0.02% oregano, 0.02% sage and 0.05% rosemary-sage added butter samples were similar to that of 0.02% BHA added samples at both 2% and 5c.…”
Section: Resultsmentioning
confidence: 99%
“…The onset of rancidity in butter may be usually due to the oxidation of unsaturated glycerides leading to the development of peroxides and/or due to hydrolysis of glycerides resulting in increased levels of free fatty acids (Joshi & Thakar, 1994;Muir, 1996). It has been reported that, both storage time and type of treatment have highly significant effects on the peroxide value and free fatty acid content of butter oil (Amr, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…The ‘ Murcchana’ samskara of ghee not only maintain the ratio of unsaturated and saturated fats but also modify the solubility pattern and absorbability of ghrita formulation [ 37 ]. Effect of antioxidant herbs on oxidative stability of cow ghee, thus their better role in preservation of food system over butylated hydroxyanisole (BHA) has been reported [ [38] , [39] , [40] , [41] , [42] , [43] ]. The herbs used in ‘ Murcchana’ process, reported with their potent antioxidant and anti-lipid peroxidation properties, play significant role in protection of ghrita from oxidative damages.…”
Section: Resultsmentioning
confidence: 99%